A new energy vehicle auxiliary battery and preparation method thereof

By using lead and nickel-modified polyester staple fiber and premixed abrasive technology mixed packages in the battery, the problems of poor charging reception capacity and insufficient cycle life of ordinary batteries are solved, and the charging and discharging efficiency and cycle life of auxiliary batteries of new energy vehicles are significantly improved.

CN119340505BActive Publication Date: 2025-04-04ZHEJIANG TIANNENG AUTOMOBILE BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411845938.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The charging reception capacity and insufficient cycle life of existing ordinary batteries, especially in new energy vehicles, low-voltage auxiliary batteries have lost power due to low DC-DC conversion charging voltage, and are difficult to recover after deep discharge, and have a short life.

Method used

Lead and nickel modified polyester staple fibers are used as the positive electrode material and negative electrode material additives for lead-acid batteries, and EFB-P01 and EFB-S04 mixing packages are obtained through premixed grinding technology to improve the conductivity and electrochemical activity of the electrode materials, and improve the charge and discharge efficiency and cycle life of the battery.

Benefits of technology

It significantly improves the charging and discharging efficiency and cycle life of the battery, and improves the charging acceptance and service life of the battery in new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a polyester staple fiber for an auxiliary battery of a new energy vehicle. The polyester staple fiber is subjected to ammonia plasma treatment and metal modification to obtain lead and nickel modified polyester staple fibers, which can improve the conductivity, electrochemical activity and mechanical properties of electrode materials, thereby improving the charge and discharge efficiency and cycle life of the battery. The invention also provides a new energy vehicle auxiliary battery and a preparation method thereof. The positive electrode lead paste and the negative electrode lead paste are both prepared by premixing and grinding technology to obtain EFB-P01 mixed material packages and EFB-S04 mixed material packages, respectively, thereby eliminating the inhibitory effect of Sb2O3 on the growth of 4BS. The sodium hydroxide solution introduced into the positive electrode lead paste can also improve the binding force between the electrode plate and the active material, further improving the cycle life capability under a partially charged state, and solving the problems of poor charging acceptance and insufficient cycle life of existing ordinary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lead-acid battery production technology, and in particular to a new energy vehicle auxiliary battery and a preparation method thereof. Background Art

[0002] With the rapid increase in sales of new energy vehicles, low-voltage auxiliary batteries are an indispensable component of new energy vehicles. If EV pure electric vehicles convert high voltage into 12 V through DC-DC to provide for on-board electrical accessories, it will cause excessive power consumption, so low-voltage auxiliary batteries are necessary, and their main function is to start the high-voltage control system and power some low-voltage electrical appliances. At the same time, low-voltage auxiliary batteries, as the power supply system for automotive electrical components (such as central locking, interior lighting, wipers, lights, on-board computers, etc.), have been continuously optimized in decades of development. The stability of lead-acid battery output performance, easy availability and low risk are advantages. Whether it is traditional fuel vehicles or the emerging new energy vehicle industry today, low-voltage lead-acid batteries are still used as the preferred power supply system for electrical components.

[0003] New energy vehicles set the charging voltage of the 12 V auxiliary battery relatively low, between 13.6-14.1V. Therefore, new requirements are put forward for the auxiliary starting battery for new energy vehicles to solve the problems of low-voltage auxiliary battery running out of power due to low DC-DC conversion charging voltage, difficulty in charging recovery after deep discharge of the battery, and short life. Improving the battery's charging acceptance capacity and cycle life has become an important issue.

[0004] The invention application with publication number CN117878434A discloses a starter battery for electric buses. The positive plate and paste process of the starter battery are composed of sulfuric acid, red lead, seed crystals, Barton lead powder and modified short fibers. The short fibers are treated with hydrochloric acid and potassium permanganate solution to optimize their activity performance, and then modified by ball milling. The mutual coordination between the raw materials is conducive to the formation of uniform tetrabasic lead sulfate under high temperature and high humidity conditions, so that the conductivity between the active material particles and between the active material and the grid is stronger and the structure is more stable. It can also significantly reduce the internal resistance of charging and discharging between the active materials and improve the battery charging acceptance capacity.

[0005] For another example, the invention application with the publication number CN116053462A discloses a lead paste formula and manufacturing method for auxiliary batteries suitable for pure electric new energy vehicles. The positive lead paste formula includes lead powder, P-40 seed crystals and ultra-short fibers; the negative lead paste formula includes lead powder, ultra-short fibers, composite carbon and SLI-A100 negative electrode auxiliary material package. In the manufacturing method, the pole group encapsulation adopts EFS-C carbon-coated PE separator to reduce the internal resistance of the battery and improve the surface conductivity of the plate. 20% to 40% of multifunctional electrolyte additives are added to the dilute sulfuric acid electrolyte in the secondary acid addition process of the battery formation to improve the conductivity of the sulfuric acid electrolyte solution, increase the solubility of lead sulfate, improve the charging acceptance performance, and at the same time increase the hydrogen evolution potential of the negative plate to reduce the water loss rate during the battery life cycle. The auxiliary battery prepared by using the lead paste formula and preparation process has the characteristics of good low-voltage charging acceptance and long cycle life under partial charge state.

[0006] Although auxiliary battery lead paste formulas have been disclosed in the prior art, it is still of great significance to develop new lead paste formulas to improve battery charging acceptance and cycle life to meet the use needs of pure electric new energy vehicles. Summary of the invention

[0007] The purpose of the present invention is to provide a new energy vehicle auxiliary battery and a preparation method thereof, which are used to solve the problems of poor charging acceptance and insufficient cycle life of existing ordinary batteries.

[0008] In order to achieve the above-mentioned object of the invention, the specific technical scheme of the present invention is as follows:

[0009] A polyester staple fiber for an auxiliary battery of a new energy vehicle. The polyester staple fiber is lead and nickel modified polyester staple fiber, wherein the lead and nickel modified polyester staple fiber has a single fiber diameter of 10-20 μm and a length of 4-5 mm.

[0010] The present invention adopts lead / nickel modified polyester staple fibers as positive electrode materials and negative electrode material additives of lead-acid batteries, which can significantly improve the electrochemical and mechanical properties of the batteries, improve the conductivity and electrochemical activity of the electrode materials, and thus improve the charge and discharge efficiency and cycle life of the batteries.

[0011] Preferably, the preparation steps of the lead and nickel modified polyester staple fibers include:

[0012] (1) By volume, 1 part of polyester staple fiber is immersed in 10-15 parts of impregnation liquid, the temperature is raised to 60-70° C., and the impregnation time is maintained at 15-22 hours, the polyester staple fiber is taken out, and dried to obtain impregnated polyester staple fiber;

[0013] (2) The impregnated polyester staple fibers are placed in a radio frequency plasma device, the radio frequency power is set to 100-200 watts, the flow rate of ammonia is controlled to 10-20 ml per minute, and a radio frequency glow plasma treatment is performed at a frequency of 27.12 MHz for a duration of 40-80 minutes to obtain lead and nickel modified polyester staple fibers.

[0014] The present invention performs ammonia plasma treatment on polyester staple fibers. Under the action of ammonia plasma, the chemical bonds on the surface of the polyester staple fibers are broken to form free radicals or ions. These active sites can combine with nitrogen atoms in ammonia, thereby introducing amino (-NH2) groups onto the surface of the polyester staple fibers.

[0015] Preferably, the composition and addition amount of the impregnation solution include, by mass: 0.008-0.03 parts of allyl(cyclopentadienyl)nickel, 2-5 parts of lead acrylate, and 100-120 parts of methylpyrrolidone.

[0016] The polyester staple fiber after the introduction of amino groups undergoes amino-olefin addition reaction with allyl (cyclopentadienyl) nickel and lead acrylate. In this process, the amino group acts as a nucleophile to attack the double bonds on the allyl or cyclopentadienyl groups to form new carbon-nitrogen bonds, while introducing lead and nickel elements into the polyester staple fiber. Through the above reaction, lead and nickel elements are successfully connected to the surface of the polyester staple fiber to form lead / nickel modified polyester staple fibers with special functions.

[0017] Preferably, the impregnation solution preparation step comprises: weighing a formula amount of allyl(cyclopentadienyl)nickel, lead acrylate and methylpyrrolidone, stirring at 60-70° C. for 100-150 minutes to obtain an impregnation solution.

[0018] The present invention also provides a new energy vehicle auxiliary battery, comprising a pole group and an electrolyte, wherein the pole group comprises a positive plate and a negative plate, the positive plate comprises a positive electrode lead paste, and the negative plate comprises a negative electrode lead paste;

[0019] The formula of positive lead paste includes lead powder, pure water, dilute sulfuric acid and positive electrode additives. The components and addition amounts of the positive electrode additives for every 1200 parts of lead powder include: 1.5-2.5 parts of polyester staple fibers, 12-18 parts of sodium hydroxide solution, and 15-20 parts of EFB-P01 mixed material package. The EFB-P01 mixed material package is a composite crystal formed by grinding 4PbO·PbSO4, SnSO4 and Sb2O3. The mass ratio of 4PbO·PbSO4, SnSO4 and Sb2O3 is (20±0.5):(10±0.2):(1±0.2). The particle size of the composite crystal is 3-6 μm.

[0020] The formula of the negative electrode lead paste includes lead powder, pure water, dilute sulfuric acid and a negative electrode additive. The components and addition amounts of the negative electrode additive corresponding to every 1200 parts of lead powder include: 1.1-1.8 parts of polyester staple fiber, 2-4 parts of carbon black, 1-3 parts of graphite, and 10-18 parts of EFB-S04 mixed material package. The EFB-S04 mixed material package is prepared by mixing and grinding barium sulfate, Norwegian A-type lignin and humic acid. The mass ratio of barium sulfate, Norwegian A-type lignin and humic acid is (3±0.5):(1.2±0.2):(1±0.2).

[0021] Wherein, the polyester staple fibers used in the positive electrode additive and the negative electrode additive are the lead and nickel modified polyester staple fibers.

[0022] The positive electrode lead paste of the present invention adds sodium hydroxide solution, which can improve the bonding force between the grid and the active material and increase the strength of the bonding force.

[0023] The EFB-P01 mixed package prepared by grinding the positive electrode lead paste premix is ​​a composite crystal that avoids the inhibitory effect of adding Sb2O3 alone on the growth of 4BS.

[0024] The EFB-S04 mixture package prepared by grinding the negative lead paste premix is ​​prepared by mixing and grinding barium sulfate, Norwegian type A lignin and humic acid. Based on this grinding method and additive ratio, the negative electrode plate has a higher charge acceptance capacity, effectively alleviating the problem of negative electrode sulfation after deep discharge.

[0025] Preferably, the density of the dilute sulfuric acid at a temperature of 27°C is 1.4 g / cm 3 .

[0026] Preferably, by mass, 10 to 40 parts of electrolyte additive are added for every 100 parts of electrolyte;

[0027] The electrolyte additives include: aluminum sulfate, lithium carbonate and potassium sulfate, wherein the mass ratio of aluminum sulfate, lithium carbonate and potassium sulfate is (5±0.2):(1±0.2):(1±0.2).

[0028] The electrolyte additive used in the present invention can be used with Pb 2+ Form coordination compounds (generally refers to compounds formed by metal atoms or ion holes and molecules or ions containing lone pairs of electrons through coordination bonds), and Pb 2+ The coordination compound formed on the lead sulfate on the plate surface by the sulfate added to the electrolyte is unstable in the acidic medium, which causes some non-conductive lead sulfate to dissolve back into the electrolyte; therefore, adding additives such as aluminum sulfate, lithium carbonate and potassium sulfate to the electrolyte can prevent sulfation, inhibit early capacity exhaustion, and improve energy density and low-temperature starting performance.

[0029] The present invention also provides a method for preparing the auxiliary battery of the new energy vehicle, and the method for preparing the positive electrode lead paste comprises the following steps:

[0030] (1) First, mix the EFB-P01 mixing bag, lead powder and polyester staple fibers, add some pure water and stir. The water adding time is controlled within 1 to 3 minutes, and the stirring time is 5 to 10 minutes.

[0031] (2) Add sodium hydroxide solution and stir for 1-2 minutes, then add the remaining amount of pure water and stir. The water addition time should be controlled within 3-5 minutes, and stir for 5-10 minutes.

[0032] (3) Add dilute sulfuric acid and control the acid addition time to 8-15 minutes;

[0033] (4) Turn on the cooling function to reduce the lead paste temperature to 49 °C to obtain the positive electrode lead paste;

[0034] The preparation method of negative electrode lead paste comprises the following steps:

[0035] (1) First, mix the EFB-S04 mixing bag, carbon black, graphite, lead powder and polyester staple fiber, add pure water and stir. The water adding time is controlled within 3-5 minutes and the stirring time is 5-10 minutes.

[0036] (2) Add dilute sulfuric acid and control the acid addition time to 8-15 minutes;

[0037] (3) Turn on the cooling function to reduce the lead paste temperature to 49 °C to obtain the negative electrode lead paste.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The present invention provides a polyester staple fiber for an auxiliary battery of a new energy vehicle. The polyester staple fiber is treated with ammonia plasma and metal-modified to obtain lead- and nickel-modified polyester staple fibers, which can improve the conductivity, electrochemical activity and mechanical properties of the electrode material, thereby improving the charge and discharge efficiency and cycle life of the battery;

[0040] (2) In the new energy vehicle auxiliary battery provided by the present invention, the positive electrode lead paste and the negative electrode lead paste are respectively obtained by pre-mixing and grinding technology to obtain EFB-P01 mixed material package and EFB-S04 mixed material package, thereby eliminating the inhibitory effect of Sb2O3 on the growth of 4BS. The sodium hydroxide solution introduced into the positive electrode lead paste can also improve the binding force between the electrode plate and the active material, further improving the cycle life capability under partial charge state, and solving the problems of poor charging acceptance and insufficient cycle life of existing ordinary batteries. DETAILED DESCRIPTION

[0041] Example 1

[0042] Pretreatment of polyester staple fibers:

[0043] (1) The preparation of the impregnation solution includes: first weighing 0.008 parts of allyl (cyclopentadienyl) nickel, 2 parts of lead acrylate, and 100 parts of methyl pyrrolidone by weight, stirring at 60 ° C for 100 minutes to obtain an impregnation solution;

[0044] (2) The polyester staple fibers are modified to obtain lead and nickel modified polyester staple fibers, the specific steps comprising:

[0045] A1 Steps:

[0046] Weigh the polyester staple fiber, the density of the polyester staple fiber is 1.33 g / cm 3 , by volume, immersing the polyester staple fiber in an impregnation liquid, wherein the volume of the impregnation liquid is 10 times the volume of the polyester staple fiber, heating to 60° C., and maintaining the impregnation time for 15 hours; taking out the polyester staple fiber, drying it, and obtaining impregnated polyester staple fiber;

[0047] A2 Steps:

[0048] Plasma treatment: the impregnated polyester staple fibers obtained in step A1 are placed in a radio frequency plasma device, and the radio frequency power is set to 100 watts; the flow rate of ammonia is controlled to 10 ml per minute; a radio frequency glow plasma treatment is used with a frequency of 27.12 MHz, and the duration is 40 minutes; and the lead and nickel modified polyester staple fibers are taken out.

[0049] The preparation method of positive lead paste is as follows:

[0050] (1) Weigh the raw materials according to the formula of positive lead paste, including 12 parts of lead powder and 1 part of pure water, with a density of 1.4g / cm 3 0.85 parts of dilute sulfuric acid (temperature 27°C), 0.015 parts of lead and nickel modified polyester staple fibers, 0.12 parts of sodium hydroxide solution, and 0.15 parts of EFB-P01 mixed material package;

[0051] (2) First, mix the EFB-P01 mixing bag, lead powder, and lead and nickel modified polyester staple fibers and stir them evenly, add 15% of the total amount of pure water, control the time of adding pure water to 1 min, and stir for 5 min;

[0052] (3) Add sodium hydroxide solution and stir for 1 min;

[0053] (4) Add the remaining pure water, add the pure water for 3 minutes, and stir for 5 minutes;

[0054] (5) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled at 8 min;

[0055] (6) Finally, start cooling to reduce the temperature of the positive electrode lead paste to 49 °C to obtain the positive electrode lead paste.

[0056] The preparation method of negative electrode lead paste is as follows:

[0057] (1) Weigh the raw materials according to the formula of negative electrode lead paste. By mass, there are 12 parts of lead powder and 1.2 parts of pure water. The density is 1.4 g / cm 3 0.9 parts of dilute sulfuric acid (temperature 27°C), 0.011 parts of lead and nickel modified polyester staple fibers, 0.02 parts of carbon black, 0.01 parts of graphite, and 0.1 parts of EFB-S04 mixed material package;

[0058] (2) First, mix the EFB-S04 mixed material package, carbon black, graphite, lead powder, and lead and nickel modified polyester staple fibers and stir them evenly, add 15% of the total amount of pure water, control the time of adding pure water to 1 min, and stir for 5 min;

[0059] (3) Add the remaining pure water, add the pure water for 3 minutes, and stir for 5 minutes;

[0060] (4) Then add dilute sulfuric acid, and control the acid addition time to 8 minutes;

[0061] (5) Finally, the cooling process is started and the lead paste temperature is reduced to 49 °C to obtain the negative electrode lead paste.

[0062] Battery Manufacturing:

[0063] The lead paste is transferred to the paste coating hopper through the unloading trolley, and evenly coated on the surface of the mesh belt by the plate coating machine. The mesh belt is then cut to produce single wet electrode plates. After the single wet electrode plates pass through the surface drying kiln, they are stacked on the curing rack by the automatic plate collecting machine, and then transferred to the curing room and cured into dry raw boards through the curing process.

[0064] The encapsulation uses the Riptide low internal resistance PE separator produced by a certain company to encapsulate the negative electrode. The battery assembly uses a COS casting welding machine to immerse the encapsulated pole group and the pole lugs in the lead-melting mold upside down, and quickly cool the pole lugs of the positive and negative plates in parallel by casting welding. Then the welded pole group is loaded into the battery slot through an auxiliary fixture, and a large current is applied to the pole column connector of the pole group through a fully automatic through-wall welding machine to melt the connector and maintain pressure to complete the through-wall welding. After the through-wall welding is completed, the middle cover heat sealing, terminal welding and airtightness detection processes are carried out.

[0065] The battery was subsequently charged using 1.190 g / cm 3The dilute sulfuric acid solution is used for primary acid addition, and the direct current charging process is used for charging. After the formation, acid is poured and secondary acid addition is performed. 10% of electrolyte additives are added to the dilute sulfuric acid for secondary acid addition. The composition and weight ratio of the electrolyte additives are aluminum sulfate: lithium carbonate: potassium sulfate = 4.8:0.8:0.8. Secondary acid addition is performed on each cell of the battery, and the liquid level height is adjusted to control the acid density to 1.290 g / cm 3 , and finally the small cover is heat-sealed, air-tightness tested, and finally the high current test and battery cleaning and drying are carried out.

[0066] Example 2

[0067] Pretreatment of polyester staple fibers:

[0068] (1) The preparation of the impregnation solution includes: weighing 0.01 parts of allyl (cyclopentadienyl) nickel, 3 parts of lead acrylate, and 107 parts of methyl pyrrolidone by weight, stirring at 65 ° C for 120 minutes to obtain an impregnation solution;

[0069] (2) The polyester staple fibers are modified with lead and nickel to obtain lead and nickel modified polyester staple fibers, the specific steps comprising:

[0070] A1 Steps:

[0071] Weigh the polyester staple fiber, the density of the polyester staple fiber is 1.33 g / cm 3 , by volume, immersing the polyester staple fiber in an impregnation liquid, wherein the volume of the impregnation liquid is 12 times the volume of the polyester staple fiber, and then heating to 64° C. and maintaining the impregnation time for 17 hours; taking out the polyester staple fiber, and drying it to obtain impregnated polyester staple fiber;

[0072] A2 Steps:

[0073] Plasma treatment: the impregnated polyester staple fibers obtained in step A1 are placed in a radio frequency plasma device, and the radio frequency power is set to 150 watts; the flow rate of ammonia is controlled to 12 ml per minute; a radio frequency glow plasma treatment is used with a frequency of 27.12 MHz, and the duration is 60 minutes; and the lead and nickel modified polyester staple fibers are taken out.

[0074] The preparation method of positive lead paste is as follows:

[0075] (1) Weigh the raw materials according to the formula of positive lead paste. By mass, there are 12 parts of lead powder and 1.05 parts of pure water. The density is 1.4 g / cm 3 0.92 parts of dilute sulfuric acid (temperature 27°C), 0.02 parts of lead and nickel modified polyester staple fibers, 0.16 parts of sodium hydroxide solution, and 0.18 parts of EFB-P01 mixed material package;

[0076] (2) First, mix the EFB-P01 mixing bag, carbon black, graphite, lead powder, and lead and nickel modified polyester staple fibers and stir them evenly, then add 22.5% of the total amount of pure water. The time for adding pure water is controlled within 2 minutes and the mixture is stirred for 7 minutes.

[0077] (3) Add sodium hydroxide solution and stir for 1.5 min;

[0078] (4) Add the remaining pure water, add the pure water for 4 min, and stir for 7.5 min;

[0079] 5) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled at 12 min;

[0080] (6) Finally, start cooling to reduce the temperature of the positive electrode lead paste to 49 °C to obtain the positive electrode lead paste.

[0081] The preparation method of negative electrode lead paste is as follows:

[0082] (1) Weigh the raw materials according to the negative electrode lead paste formula, including 12 parts of lead powder and 1.25 parts of pure water, with a density of 1.4 g / cm 3 0.95 parts of dilute sulfuric acid (temperature 27°C), 0.015 parts of lead and nickel modified polyester staple fibers, 0.03 parts of carbon black, 0.02 parts of graphite, and 0.14 parts of EFB-S04 mixed material package;

[0083] (2) First, mix the EFB-S04 mixed material package, carbon black, graphite, lead powder, and lead and nickel modified polyester staple fibers and stir them evenly, then add 22% of the total amount of pure water, control the time of adding pure water to 2 minutes, and stir for 7 minutes;

[0084] (3) Add the remaining pure water, add the pure water for 4 minutes, and stir for 7 minutes;

[0085] (4) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled at 12 min;

[0086] (5) Finally, the cooling process is started and the lead paste temperature is reduced to 49 °C to obtain the negative electrode lead paste.

[0087] The lead paste is transferred to the paste coating hopper through the unloading trolley, and evenly coated on the surface of the mesh belt by the plate coating machine. The mesh belt is then cut to produce single wet electrode plates. After the single wet electrode plates pass through the surface drying kiln, they are stacked on the curing rack by the automatic plate collecting machine, and then transferred to the curing room and cured into dry raw boards through the curing process.

[0088] The encapsulation uses the Riptide low internal resistance PE separator produced by a certain company to encapsulate the negative electrode. The battery assembly uses a COS casting welding machine to immerse the encapsulated pole group and the pole lugs in the lead-melting mold upside down, and quickly cool the pole lugs of the positive and negative plates in parallel by casting welding. Then the welded pole group is loaded into the battery slot through an auxiliary fixture, and a large current is applied to the pole column connector of the pole group through a fully automatic through-wall welding machine to melt the connector and maintain pressure to complete the through-wall welding. After the through-wall welding is completed, the middle cover heat sealing, terminal welding and airtightness detection processes are carried out.

[0089] The battery was subsequently charged using 1.190 g / cm 3 The dilute sulfuric acid solution is used for primary acid addition, and the direct current charging process is used for charging. After the formation, acid is poured and secondary acid addition is performed. 25% of electrolyte additives are added to the dilute sulfuric acid for secondary acid addition. The composition and weight ratio of the electrolyte additives are aluminum sulfate: lithium carbonate: potassium sulfate = 5:1:1. Secondary acid addition is performed on each cell of the battery, and the liquid level is adjusted to control the acid density to 1.295 g / cm 3 , and finally the small cover is heat-sealed, air-tightness tested, and finally the high current test and battery cleaning and drying are carried out.

[0090] Example 3

[0091] Pretreatment of polyester staple fibers:

[0092] (1) The preparation of the impregnation solution includes: weighing 0.03 parts of allyl (cyclopentadienyl) nickel, 5 parts of lead acrylate, and 120 parts of methyl pyrrolidone by weight, stirring at 70 ° C for 150 min to obtain an impregnation solution;

[0093] (2) The polyester staple fibers are modified with lead and nickel to obtain lead and nickel modified polyester staple fibers, the specific steps comprising:

[0094] A1 Steps:

[0095] Weigh the polyester staple fiber, the density of the polyester staple fiber is 1.33 g / cm 3 , by volume, immersing the polyester staple fiber in an impregnation liquid, wherein the volume of the impregnation liquid is 15 times the volume of the polyester staple fiber, and then heating to 70°C and maintaining the impregnation time for 22 hours; taking out the polyester staple fiber and drying it to obtain impregnated polyester staple fiber;

[0096] A2 Steps:

[0097] Plasma treatment: the impregnated polyester staple fibers obtained in step A1 are placed in a radio frequency plasma device, and the radio frequency power is set to 200 watts; the flow rate of ammonia is controlled to 20 ml per minute; a radio frequency glow plasma treatment is used with a frequency of 27.12 MHz, and the duration is 80 minutes; and the lead and nickel modified polyester staple fibers are taken out.

[0098] The preparation method of positive lead paste is as follows:

[0099] (1) Weigh the raw materials according to the formula of positive lead paste. By mass, the lead powder is 12 parts, the pure water is 1.15 parts, and the density is 1.4 g / cm 3 0.85 parts of dilute sulfuric acid (temperature 27°C), 0.018 parts of lead and nickel modified polyester staple fibers, 0.2 parts of sodium hydroxide solution, and 0.2 parts of EFB-P01 mixed material package;

[0100] (2) First, mix the EFB-P01 mixing bag, carbon black, graphite, lead powder, and lead and nickel modified polyester staple fibers, and stir them evenly. Then, add 30% of the total amount of pure water. The time for adding pure water is controlled within 3 minutes, and stir for 10 minutes.

[0101] (3) Add sodium hydroxide solution and mix and stir for 2 minutes;

[0102] (4) Add the remaining pure water, add the pure water for 5 min, and stir for 10 min;

[0103] (5) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled within 15 min;

[0104] (6) Finally, start cooling to reduce the temperature of the positive electrode lead paste to 49 °C to obtain the positive electrode lead paste.

[0105] The preparation method of negative electrode lead paste is as follows:

[0106] (1) Weigh the raw materials according to the negative electrode lead paste formula, including 12 parts of lead powder and 1.35 parts of pure water, with a density of 1.4 g / cm 3 1 part of dilute sulfuric acid (temperature 27°C), 0.018 parts of lead and nickel modified polyester staple fibers, 0.04 parts of carbon black, 0.03 parts of graphite, and 0.18 parts of EFB-S04 mixed material package;

[0107] (2) First, mix the EFB-S04 mixed material package, carbon black, graphite, lead powder, and lead and nickel modified polyester staple fibers and stir them evenly, add 30% of the total amount of pure water, control the time of adding pure water to 3 minutes, and stir for 10 minutes;

[0108] (3) Add the remaining pure water, control the time of adding pure water to 5 minutes, and stir for 10 minutes;

[0109] (4) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled within 15 min;

[0110] (5) Finally, the cooling process is started and the lead paste temperature is reduced to 49 °C to obtain the negative electrode lead paste.

[0111] The lead paste is transferred to the paste coating hopper through the unloading trolley, and evenly coated on the surface of the mesh belt by the plate coating machine. The mesh belt is then cut to produce single wet electrode plates. After the single wet electrode plates pass through the surface drying kiln, they are stacked on the curing rack by the automatic plate collecting machine, and then transferred to the curing room and cured into dry raw boards through the curing process.

[0112] The encapsulation uses the Riptide low internal resistance PE separator produced by a certain company to encapsulate the negative electrode. The battery assembly uses a COS casting welding machine to immerse the encapsulated pole group and the pole lugs in the lead-melting mold upside down, and quickly cool the pole lugs of the positive and negative plates in parallel by casting welding. Then the welded pole group is loaded into the battery slot through an auxiliary fixture, and a large current is applied to the pole column connector of the pole group through a fully automatic through-wall welding machine to melt the connector and maintain pressure to complete the through-wall welding. After the through-wall welding is completed, the middle cover heat sealing, terminal welding and airtightness detection processes are carried out.

[0113] The battery was subsequently charged using 1.190 g / cm 3 The dilute sulfuric acid solution is used for primary acid addition, and the direct current charging process is used for charging. After the formation, acid is poured and secondary acid addition is performed. 40% of electrolyte additives are added to the dilute sulfuric acid for secondary acid addition. The composition and weight ratio of the electrolyte additives are aluminum sulfate: lithium carbonate: potassium sulfate = 5.2:1.2:1.2. Secondary acid addition is performed on each cell of the battery, and the liquid level is adjusted to control the acid density to 1.295±0.005 g / cm 3 , and finally the small cover is heat-sealed, air-tightness tested, and finally the high current test and battery cleaning and drying are carried out.

[0114] Comparative Example 1

[0115] The preparation method of positive lead paste is as follows:

[0116] (1) Weigh the raw materials according to the formula of positive lead paste, including 12 parts of lead powder and 1 part of pure water, with a density of 1.4g / cm 3 0.85 parts of dilute sulfuric acid (temperature 27°C), 0.015 parts of polyester staple fiber not modified with lead and nickel, 0.12 parts of sodium hydroxide solution, and 0.15 parts of EFB-P01 mixed bag;

[0117] (2) First, mix the EFB-P01 mixing bag, lead powder and polyester staple fibers that are not modified with lead and nickel, add 15% of the total amount of pure water, control the time of adding pure water to 1 min, and stir for 5 min;

[0118] (3) Add sodium hydroxide solution and stir for 1 min;

[0119] (4) Add the remaining pure water, add the pure water for 3 minutes, and stir for 5 minutes;

[0120] (5) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled at 8 min;

[0121] (6) Finally, start cooling to reduce the temperature of the positive electrode lead paste to 49 °C to obtain the positive electrode lead paste.

[0122] The preparation method of negative electrode lead paste is as follows:

[0123] (1) Weigh the raw materials according to the formula of negative electrode lead paste. By mass, there are 12 parts of lead powder and 1.2 parts of pure water. The density is 1.4 g / cm 3 0.9 parts of dilute sulfuric acid (temperature 27°C), 0.011 parts of polyester staple fibers not modified with lead and nickel, 0.02 parts of carbon black, 0.01 parts of graphite, and 0.1 parts of EFB-S04 mixed material package;

[0124] (2) First, mix the EFB-S04 mixed material package, carbon black, graphite, lead powder, and lead and nickel modified polyester staple fibers and stir them evenly, add 15% of the total amount of pure water, control the time of adding pure water to 1 min, and stir for 5 min;

[0125] (3) Add the remaining pure water, add the pure water for 3 minutes, and stir for 5 minutes;

[0126] (4) Then add dilute sulfuric acid, and control the acid addition time to 8 minutes;

[0127] (5) Finally, the cooling process is started and the lead paste temperature is reduced to 49 °C to obtain the negative electrode lead paste.

[0128] Battery Manufacturing:

[0129] The lead paste is transferred to the paste coating hopper through the unloading trolley, and evenly coated on the surface of the mesh belt by the plate coating machine. The mesh belt is then cut to produce single wet electrode plates. After the single wet electrode plates pass through the surface drying kiln, they are stacked on the curing rack by the automatic plate collecting machine, and then transferred to the curing room and cured into dry raw boards through the curing process.

[0130] The encapsulation uses the Riptide low internal resistance PE separator produced by a certain company to encapsulate the negative electrode. The battery assembly uses a COS casting welding machine to immerse the encapsulated pole group and the pole lugs in the lead-melting mold upside down, and quickly cool the pole lugs of the positive and negative plates in parallel by casting welding. Then the welded pole group is loaded into the battery slot through an auxiliary fixture, and a large current is applied to the pole column connector of the pole group through a fully automatic through-wall welding machine to melt the connector and maintain pressure to complete the through-wall welding. After the through-wall welding is completed, the middle cover heat sealing, terminal welding and airtightness detection processes are carried out.

[0131] The battery was subsequently charged using 1.190 g / cm 3 The dilute sulfuric acid solution is used for primary acid addition, and the direct current charging process is used for charging. After the formation, acid is poured and secondary acid addition is performed. 10% of electrolyte additives are added to the dilute sulfuric acid for secondary acid addition. The composition and weight ratio of the electrolyte additives are aluminum sulfate: lithium carbonate: potassium sulfate = 4.8:0.8:0.8. Secondary acid addition is performed on each cell of the battery, and the liquid level height is adjusted to control the acid density to 1.290 g / cm 3 , and finally the small cover is heat-sealed, air-tightness tested, and finally the high current test and battery cleaning and drying are carried out.

[0132] Comparative Example 2

[0133] Pretreatment of polyester staple fibers:

[0134] (1) The preparation of the impregnation solution includes: weighing 0.03 parts of allyl (cyclopentadienyl) nickel, 5 parts of lead acrylate, and 120 parts of methyl pyrrolidone by weight, stirring at 70 ° C for 150 min to obtain an impregnation solution;

[0135] (2) The polyester staple fibers are modified with lead and nickel to obtain lead and nickel modified polyester staple fibers, the specific steps comprising:

[0136] A1 Steps:

[0137] Weigh the polyester staple fiber, the density of the polyester staple fiber is 1.33 g / cm 3 , by volume, immersing the polyester staple fiber in an impregnation liquid, wherein the volume of the impregnation liquid is 15 times the volume of the polyester staple fiber, heating to 70°C, and maintaining the impregnation time for 22 hours; taking out the polyester staple fiber, drying it, and obtaining impregnated polyester staple fiber;

[0138] A2 Steps:

[0139] Plasma treatment: the impregnated polyester staple fibers obtained in step A1 are placed in a radio frequency plasma device, and the radio frequency power is set to 200 watts; the flow rate of ammonia is controlled to 20 ml per minute; a radio frequency glow plasma treatment is used with a frequency of 27.12 MHz, and the duration is 80 minutes; and the lead and nickel modified polyester staple fibers are taken out.

[0140] The preparation method of positive lead paste is as follows:

[0141] (1) Weigh the raw materials according to the formula of positive lead paste, including 12 parts of lead powder and 1 part of pure water, with a density of 1.4g / cm 3 0.85 parts of dilute sulfuric acid (temperature 27°C), 0.015 parts of polyester staple fibers modified with lead and nickel, 0.12 parts of sodium hydroxide solution, and 0.008 parts of antimony trioxide;

[0142] (2) First, mix the lead powder, lead and nickel modified polyester staple fibers and antimony trioxide and stir evenly, add 15% of the total amount of pure water, control the time of adding pure water to 1 min, and stir for 5 min;

[0143] (3) Add sodium hydroxide solution and stir for 1 min;

[0144] (4) Add the remaining pure water, add the pure water for 3 minutes, and stir for 5 minutes;

[0145] (5) Then add dilute sulfuric acid (density 1.4 g / cm at 27 °C) 3 ), the acid addition time is controlled at 8 min;

[0146] (6) Finally, start cooling to reduce the temperature of the positive electrode lead paste to 49 °C to obtain the positive electrode lead paste.

[0147] The preparation method of negative electrode lead paste is as follows:

[0148] (1) Weigh the raw materials according to the formula of negative electrode lead paste. By mass, there are 12 parts of lead powder and 1.2 parts of pure water. The density is 1.4 g / cm 3 0.9 parts of dilute sulfuric acid (temperature 27°C), 0.011 parts of polyester staple fibers modified with lead and nickel, 0.02 parts of carbon black, 0.01 parts of graphite, and 0.03 parts of lignin;

[0149] (2) First, carbon black, graphite, lead powder, lignin, and lead and nickel modified polyester staple fibers were mixed and stirred evenly, and 15% of the total amount of pure water was added. The time of adding pure water was controlled within 1 min, and the mixture was stirred for 5 min.

[0150] (3) Add the remaining pure water, add the pure water for 3 minutes, and stir for 5 minutes;

[0151] (4) Then add dilute sulfuric acid, and control the acid addition time to 8 minutes;

[0152] (5) Finally, the cooling process is started and the lead paste temperature is reduced to 49 °C to obtain the negative electrode lead paste.

[0153] Battery Manufacturing:

[0154] The lead paste is transferred to the paste coating hopper through the unloading trolley, and evenly coated on the surface of the mesh belt by the plate coating machine. The mesh belt is then cut to produce single wet electrode plates. After the single wet electrode plates pass through the surface drying kiln, they are stacked on the curing rack by the automatic plate collecting machine, and then transferred to the curing room and cured into dry raw boards through the curing process.

[0155] The encapsulation uses the Riptide low internal resistance PE separator produced by a certain company to encapsulate the negative electrode. The battery assembly uses a COS casting welding machine to immerse the encapsulated pole group and the pole lugs in the lead-melting mold upside down, and quickly cool the pole lugs of the positive and negative plates in parallel by casting welding. Then the welded pole group is loaded into the battery slot through an auxiliary fixture, and a large current is applied to the pole column connector of the pole group through a fully automatic through-wall welding machine to melt the connector and maintain pressure to complete the through-wall welding. After the through-wall welding is completed, the middle cover heat sealing, terminal welding and airtightness detection processes are carried out.

[0156] The battery was subsequently charged using 1.190 g / cm 3 The dilute sulfuric acid solution is used for primary acid addition, and the direct current charging process is used for charging. After the formation, acid is poured and secondary acid addition is performed. 10% of electrolyte additives are added to the dilute sulfuric acid for secondary acid addition. The composition and weight ratio of the electrolyte additives are aluminum sulfate: lithium carbonate: potassium sulfate = 4.8:0.8:0.8. Secondary acid addition is performed on each cell of the battery, and the liquid level height is adjusted to control the acid density to 1.290 g / cm 3 , and finally the small cover is heat-sealed, air-tightness tested, and finally the high current test and battery cleaning and drying are carried out.

[0157] Test Example 1

[0158] The embodiment and the comparative example were manufactured according to the same process, and the battery model was 54565. The cycle life and static charge acceptance at 27°C and 17.5% DOD were tested according to the GB / T43346-2023 test standard, and the comparative test life results are shown in Table 1.

[0159] Table 1

[0160]

[0161] It can be seen from the results in Table 1 that the cycle life of Examples 1 to 3 is better than that of the comparative example, indicating that the mixed package seed, the polyester staple fiber modified with lead and nickel, and the sodium hydroxide solution in the positive electrode lead paste formula can improve the cycle life capability under partial charge state, and the static charge acceptance of Examples 1 to 3 is better than that of the comparative example, indicating that the mixed package in the negative electrode lead paste formula and the novel electrolyte additive can significantly improve the charge acceptance; while the cycle life and charge acceptance of Comparative Example 1 (polyester staple fiber modified with lead and nickel is not used but the mixed package is used) and Comparative Example 2 (polyester staple fiber modified with lead and nickel is used but the mixed package is not used) are worse than those of Examples 1 to 3.

Claims

1. A polyester staple fiber for auxiliary batteries of new energy vehicles, characterized in that: The polyester staple fiber is lead and nickel modified polyester staple fiber, and the preparation steps of the lead and nickel modified polyester staple fiber include: (1) By volume, 1 part of polyester staple fiber is immersed in 10-15 parts of an impregnation liquid, the temperature is raised to 60-70° C., and the impregnation time is maintained at 15-22 hours, the polyester staple fiber is taken out, and air-dried to obtain an impregnated polyester staple fiber, wherein the impregnation liquid comprises, by mass, 0.008-0.03 parts of allyl (cyclopentadienyl) nickel, 2-5 parts of lead acrylate, and 100-120 parts of methyl pyrrolidone; (2) placing the impregnated polyester staple fibers in a radio frequency plasma device, setting the radio frequency power to 100-200 watts, controlling the flow rate of ammonia to 10-20 ml per minute, using a radio frequency glow plasma treatment at a frequency of 27.12 MHz for a duration of 40-80 minutes, and taking out the lead and nickel modified polyester staple fibers; Among them, the single fiber diameter of lead and nickel modified polyester staple fibers is 10~20 μm and the length is 4~5 mm.

2. The polyester staple fiber according to claim 1, characterized in that: The impregnation solution preparation step comprises: weighing the formulated amounts of allyl (cyclopentadienyl) nickel, lead acrylate and methyl pyrrolidone, stirring at 60-70° C. for 100-150 minutes to obtain the impregnation solution.

3. A new energy vehicle auxiliary battery, characterized in that: It includes an electrode group and an electrolyte, wherein the electrode group includes a positive electrode plate and a negative electrode plate, the positive electrode plate includes a positive electrode lead paste, and the negative electrode plate includes a negative electrode lead paste; The formula of positive lead paste includes lead powder, pure water, dilute sulfuric acid and positive electrode additives. The components and addition amounts of the positive electrode additives for every 1200 parts of lead powder include: 1.5-2.5 parts of polyester staple fibers, 12-18 parts of sodium hydroxide solution, and 15-20 parts of EFB-P01 mixed material package. The EFB-P01 mixed material package is a composite crystal formed by grinding 4PbO·PbSO4, SnSO4 and Sb2O3. The mass ratio of 4PbO·PbSO4, SnSO4 and Sb2O3 is (20±0.5):(10±0.2):(1±0.2). The particle size of the composite crystal is 3-6 μm. The formula of the negative electrode lead paste includes lead powder, pure water, dilute sulfuric acid and a negative electrode additive. The components and addition amounts of the negative electrode additive corresponding to every 1200 parts of lead powder include: 1.1-1.8 parts of polyester staple fiber, 2-4 parts of carbon black, 1-3 parts of graphite, and 10-18 parts of EFB-S04 mixed material package. The EFB-S04 mixed material package is prepared by mixing and grinding barium sulfate, Norwegian A-type lignin and humic acid. The mass ratio of barium sulfate, Norwegian A-type lignin and humic acid is (3±0.5):(1.2±0.2):(1±0.2). Among them, the polyester staple fibers used in the positive electrode additive and the negative electrode additive are the polyester staple fibers for the auxiliary battery of new energy vehicles as described in any one of claims 1 to 2.

4. The new energy vehicle auxiliary battery according to claim 3, characterized in that: The density of the dilute sulfuric acid at a temperature of 27°C is 1.4 g / cm 3 .

5. The new energy vehicle auxiliary battery according to claim 3 or 4, characterized in that: By mass, 10 to 40 parts of electrolyte additives are added for every 100 parts of electrolyte; The electrolyte additives include: aluminum sulfate, lithium carbonate and potassium sulfate, wherein the mass ratio of aluminum sulfate, lithium carbonate and potassium sulfate is (5±0.2):(1±0.2):(1±0.2).

6. The method for preparing a new energy vehicle auxiliary battery according to any one of claims 3 to 5, characterized in that: The preparation method of positive lead paste comprises the following steps: (1) First, mix the EFB-P01 mixing bag, lead powder and polyester staple fibers, add some pure water and stir. The water adding time is controlled within 1 to 3 minutes, and the stirring time is 5 to 10 minutes. (2) Add sodium hydroxide solution and stir for 1-2 minutes, then add the remaining amount of pure water and stir. The water addition time should be controlled within 3-5 minutes, and stir for 5-10 minutes. (3) Add dilute sulfuric acid and control the acid addition time to 8-15 minutes; (4) Turn on the cooling function to reduce the lead paste temperature to 49 °C to obtain the positive electrode lead paste; The preparation method of negative electrode lead paste comprises the following steps: (1) First, mix the EFB-S04 mixing bag, carbon black, graphite, lead powder and polyester staple fiber, add pure water and stir. The water adding time is controlled within 3-5 minutes and the stirring time is 5-10 minutes. (2) Add dilute sulfuric acid and control the acid addition time to 8-15 minutes; (3) Turn on the cooling function to reduce the lead paste temperature to 49 °C to obtain the negative electrode lead paste.

Citation Information

Patent Citations

  • Auxiliary battery lead paste formula suitable for pure electric new energy automobile and manufacturing method

    CN116053462A

  • Special starting battery for electric bus

    CN117878434A

  • Manufacturing method of secondary cell

    JP2007048761A

  • Preparation of vicinal-chloraminoalkanes from alpha-olefins chloramines and aluminum halide catalysts

    US4089903A